1993
DOI: 10.1007/bf00284691
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, sequence analysis, and characterization of a new cell wall hydrolase, CwIL, of Bacillus licheniformis

Abstract: We have cloned a DNA fragment containing the gene for a cell wall hydrolase from Bacillus licheniformis FD0120 into Escherichia coli. Sequencing of the fragment showed the presence of an open reading frame (ORF; designated as cwlL), which is different from the B. licheniformis cell wall hydrolase gene cwlM, and encodes a polypeptide of 360 amino acids with a molecular mass of 38,994. The enzyme purified from the E. coli clone is an N-acetylmuramoyl-L-alanine amidase, which has a M(r) value of 41 kDa as determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Western blot analysis with an antibody against the N-terminal region of AtlA confirmed that the deletion oc- curred in this region. The degradation of cell wall hydrolases without a loss of enzymatic activity has been observed previously for Bacillus licheniformis (23), Bacillus subtilis (13,26), and Lactococcus lactis (3). These results suggest that the atlA gene cloned for this study encodes the major autolysin of S. mutans.…”
Section: Discussionsupporting
confidence: 65%
“…Western blot analysis with an antibody against the N-terminal region of AtlA confirmed that the deletion oc- curred in this region. The degradation of cell wall hydrolases without a loss of enzymatic activity has been observed previously for Bacillus licheniformis (23), Bacillus subtilis (13,26), and Lactococcus lactis (3). These results suggest that the atlA gene cloned for this study encodes the major autolysin of S. mutans.…”
Section: Discussionsupporting
confidence: 65%
“…The motif is composed of three -helices (Ghuysen et al, 1994) and classified in the putative peptidoglycan binding domain-1 [Pfam database]. This motif is conserved among many peptidoglycan hydrolases (e.g., SleC from C. perfringens (Miyata et al, 1995a), CwlA from B. subtilis (Kuroda and Sekiguchi, 1990), CwlL from B. licheniformis (Oda et al, 1993), DDcarboxypeptidase from Streptmyces albus (Joris et al, 1983), and autolytic lysozyme from C. acetobutylicum (Croux and Garcia, 1991)). Interestingly, when the importance of the motif in SleB localization was examined, we could discriminate the localization patterns of two fusion proteins in the gerE mutant ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall-lytic amidases in the genus Bacillus are classified into two groups; class I contains CwlA (8,22), CwlL (36), and a lytic enzyme from PBSX (XlyA) (29), and class II contains CwlB (LytC) (23,28) and CwlM (27). Furthermore, amino acid sequence homology among other autolytic enzymes suggests that a lytic enzyme of a Bacillus species (39) and a sporulation phase-specific lytic enzyme, CwlC (20), belong to class I and class II, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli and Salmonella typhimurium, the gene product (amidase) of amiB upstream of the DNA repair gene (mutL) (50) and the deduced protein of orf32 upstream of hemF (an oxygen-dependent coproporphyrinogen oxidase gene) (48,49,52) belong to the class II group. Recent reports suggest that the class I family may be lytic enzymes derived originally from phages, because the genes neighboring the lytic enzyme gene are functionally similar to phage genes (8,10,29,36). However, in spite of extensive research on autolysins, their role in cell differentiation is almost unknown.…”
Section: Discussionmentioning
confidence: 99%